An Empirical Investigation into Millennials and their Buying Behaviour within Pop-Up Retail Stores: Array - Kekana, Reabetswe; Venter de Villiers, Marike; van den Berg, Annekee; Chuchu, Tinashe (Acta Universitatis Danubius. Œconomica, 2020)
Multi-channel retailing has become increasingly popular as retailers aim to provide consumers with additional contact points. This is commonly done by means of pop-up retailing, an innovative retail concept that places significant emphasis on creating a unique in-store experience. Although a number of studies have been conducted on this topic, limited research is available on the factors that influence purchase intention in pop-up retail stores among Millennials, especially with regard to fashion products. This article investigates the influence of perceived store uniqueness, store atmosphere and product assortment on purchase intention, and the mediating effect of brand experience on the relationship between the predictor variables and purchase intention among Millennials in Johannesburg. By means of a quantitative study, 208 responses were collected in the form of self-administered questionnaires. Four proposed hypotheses were tested through structural equation modeling. The results revealed that all four hypotheses are significant, and that brand experience partially mediates the relationship between the predictor variables and purchase intention. The results provide retailers and marketing practitioners with insight into how the concept of pop-up retail stores can be utilised to maximise the brand experience and influence buying behaviour among Millennials. It consequently sheds light on the importance of creating a unique brand experience through pop-up retail as a channel to reach prospective customers. The main recommendation from the findings is, therefore, to ensure that the store atmosphere is uniquely tailored for the intended audience so as to result in positive brand experience which allows for positive word-of-mouth to be spread to prospective shoppers.